Evaluating equality in psoriasis healthcare: a cohort study of the impact of age on prescription of biologics. (1st March 2016) - Geale, K.; Henriksson, M.; Schmitt‐Egenolf, M.
Summary: Background: Inequality in healthcare has been identified in many contexts. To the best of our knowledge, this is the first study investigating age inequality in the form of prescription patterns of biologics in psoriasis care. Objectives: To determine whether patients with psoriasis have equal opportunities to receive biological medications as they age. If patients did not receive equal treatment, a subsequent objective was to determine the magnitude of the disparity. Methods: A cohort of biologic‐naive patients with psoriasis was analysed using Cox proportional hazards models to measure the impact of each additional year of life on the likelihood of initiating biological treatment, after controlling for sex, body mass index, comorbidities, disease activity and educational level. A supporting analysis used a nonparametric graphical method to study the proportion of patients initiating biological treatment as age increased, after controlling for the same covariates. Results: The Cox proportional hazards model resulted in hazard ratios of a 1‐year increase in age of 0·96–0·97 depending on calendar‐year stratification, which implies that an increase in age of 30 years corresponds to a reduced likelihood of initiating biological treatment by 61·3–67·6%. The estimated proportion of patients initiating biological medication always decreased as age increased, at a statistically significant level. Conclusions: Patients with psoriasis have fewer opportunities to access biological medications as they age. This result was shown to be applicable at all stages in a patient's life course and was not only restricted to the elderly, although it implies greater disparities as the age difference between patients increases. These results show that inequality in access to biological treatments due to age is prevalent in clinical practice today. Further research is needed to investigate the extent to which this result is influenced by patient preferences.